2017
DOI: 10.18178/ijmlc.2017.7.5.634
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Deep Learning Algorithms to Predict Customer Churn within a Local Retail Industry

Abstract: Abstract-A top priority in any business is a constant need to increase revenue and profitability. One of the causes for a decrease in profits is when current customers stop transacting. When a customer leaves or churns from a business, the opportunity for potential sales or cross selling is lost. If a customer leaves the business without any form of advice, the company may find it hard to respond and take corrective action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…For example, Paolanti et al [74] employed deep convolutional neural network (DCNN) to develop a mobile robot, so-called ROCKy, to analyze real-time store heat maps of retail store shelves for detection of the shelf-out-of-stock (SOOS) and promotional activities during working hours. Dingli, Marmara, and Fournier [75] investigated solutions to identify the patterns and features among transactional data to predict customer churn within the retail industry. To do so, they compared the performance of CNN and restricted Boltzmann machine (RBM), realizing the RBM outperformed in customer churn prediction.…”
Section: Marketingmentioning
confidence: 99%
“…For example, Paolanti et al [74] employed deep convolutional neural network (DCNN) to develop a mobile robot, so-called ROCKy, to analyze real-time store heat maps of retail store shelves for detection of the shelf-out-of-stock (SOOS) and promotional activities during working hours. Dingli, Marmara, and Fournier [75] investigated solutions to identify the patterns and features among transactional data to predict customer churn within the retail industry. To do so, they compared the performance of CNN and restricted Boltzmann machine (RBM), realizing the RBM outperformed in customer churn prediction.…”
Section: Marketingmentioning
confidence: 99%
“…The activation function is used in the Neural Network to achieve non-linear behavior otherwise it acts like a simple linear regression model or the linear model. The role and softmax are used as activation function for the hidden layers, which is optimal [20] where the problem of vanishing gradient are avoided. The sigmoid activation function performs best in the output layer, hence the same activation function is applied to the output layer.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In [12] Customer attrition related to the retail sector are analyzed using deep learning based model. The profound learning models are shaped utilizing a limited Restricted Boltzmann machine(RBM) and convolution neural network(CNN).…”
Section: Related Workmentioning
confidence: 99%
“…For example, Paolanti et al [68] employ deep convolutional neural network (DCNN) to develop a mobile robot, so called ROCKy, to analyze real-time store heat maps of retail store shelves for detection of shelf out of stock (SOOS) and promotional activities, during working hours. Dingli, Marmara, and Fournier [69] were looking for solutions to find the patterns and features among transactional data to predict customer churn within the retail industry. To do so, they compare the performance of CNN and restricted Boltzmann machine (RBM), and they found out the RBM attained outperformed in customer churn prediction.…”
Section: Other Algorithmsmentioning
confidence: 99%
“…Largescale deep learning (LSDL) and MACN are DL algorithms that are used to analyze financial time series data to predict stock price [49,55]. Ultimately, it is found that DCNN and RBM applied for analyzing primary data for respectively promotional activities [68] and customer behavior forecasting [69] (see Table 8). Hybrid deep neural networks are architectures that apply generative and discriminative components at the same time.…”
Section: Cryptocurrencymentioning
confidence: 99%